Salutogeneze a behaviorální medicína - Krivohlavý, J (Casopis lekaru ceskych, 1990)
As the opposite number of the classical biomedical model the author presents the bio-psycho-social model which attempts to supplement relatively omitted subjects of health and disease. Against the emphasis on pathogenesis he puts salutogenesis--problems leading to "firm health", a good health status despite unfavourable and risk factors, and health promotion. Behavioural medicine associates with this concept the problem of social influences on the development of diseases and their prevention and treatment. At the same time he pays attention to lifestyle, living pattern, habits, attitudes, behaviour and action which influence the health status. The author gives an account of theoretical concepts, subjects and emphasizes aspects of this approach.
Keywords: podpora zdraví; zdravotní výchova; lidé; behaviorální lékařství; Life Style; Health Promotion; Humans; životní styl; Health Education; Behavioral Medicine